Антибактеріальна активність гідрогелевих матеріалів на основі кополімерів полівінілпіролідону з екстрактами Calendula officinalis і Arnica montana - Суберляк, С. А.; Петріна, Р. О.; Гриценко, О. М.; Федорова, О. В.; Suberliak, S.; Petrina, R.; Grytsenko, O.; Fedorova, O. (Lviv Politechnic Publishing House, 2020)
Встановлено можливість використання гідрогелів на основі кополімерів полівініл- піролідону з 2-гідроксиетилметакрилатом для насичення їх рослинними екстрактами. Одержано гідрогелеві матеріали з екстрактами Calendula officinalis і Arnica montana. Визна- чено сорбційну здатність гідрогелів щодо рослинних екстрактів та вміст флавоноїдів у них. Досліджено бактерицидну та фунгіцидну активність одержаних гідрогельних матеріалів з екстрактами Calendula officinalis і Arnica montana щодо бактерій Escherichiacoli, Staphylococcusaureus та грибів Candidatenuis, Aspergilusniger.

The possibility of using hydrogels,that are based on copolymers of polyvinylpyrrolidone with 2-hydroxyethylmethacrylate for saturation them with extracts of plants,was researched. Hydrogel materials with extracts of Calendula officinal is and Arnica montana were obtained. The sorption capacity of the hydrogels in relation to these extracts and the content of flavonoids in the extracts were determined by using Ulab108UV. The bactericidal and fungicidal activity of the obtained hydrogel materials with the extracts of Calendula officinal is and Arnica montana on bacterial strains of Escherichia coli, Staphylococcus aureus and fungal strains of Candida tenuis and Aspergilus niger were investigated.
Antibacterial activity of hydrogel materials based on copolymers polyvinylpirrolidon with extracts of Calendula officinalis and Arnica Montana
Keywords: гідрогелі; екстракт; флавоноїди; антибактеріальна та фунгіцидна активності; Calendula officinalis; Arnicamontana; hydrogel; flavonoids; antibacterial activity; antifungal activity; extract; Calendula officinalis; Arnica montana